Peran Koperasi Sekolah dalam Menumbuhkan Jiwa Kewirausahaan pada Siswa SMP - Widya Nuriyanti; Husain Nurisman; Toto Widiarto; Sutina Sutina; Zeinora Zeinora; Arief Muda Kusuma; Sigit Widiyarto; Lidya Natalia Sartono (Journal on Education, 2023)
This study discusses the important role of cooperatives in fostering an entrepreneurial spirit in junior high school students. The role of cooperatives makes an important contribution to the journey of the economy in Indonesia. Cooperatives, which have always been the pillars of economics, have become one of the platforms for fostering an entrepreneurial spirit in junior high school students. The research method uses descriptive qualitative methods. The research was conducted at one of the junior high schools in the city of Tangerang. This study uses a qualitative method. Data was collected through interviews and documentation. The results of the study show that entrepreneurial learning cooperatives can be carried out through school cooperatives. The role of school cooperatives is important, especially to encourage entrepreneurial practice activities in schools. The school cooperative entrepreneurship learning process begins with providing insight (training and mentoring) Keywords: cooperatives, entrepreneurship, junior high school students Abstrak Penelitian ini membahas peran penting koperasi dalam menumbuhkan jiwa kewirausahaan pada siswa SMP. Peran koperasi memberikan kontribusi penting dalam perjalanan perekonomian di Indonesia. Koperasi yang sejak dulu menjadi soko guru perekonomian menjadi salah satu wadah dalam menumbuhkan jiwa wirausaha pada siswa SMP. Metode penelitian menggunakan metode kualitatif deskriptif. Penelitian dilakukan pada salah satu SMP yang berada di kota Tangerang. Penelitian ini menggunakan metode kualitatif. Data diambil melalui wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa koperasi Pembelajaran kewirausahaan dapat dilakukan melalui koperasi sekolah. Peran koperasi sekolah penting, terutama untuk mendorong kegiatan praktek kewirausaan di sekolah. Proses pembelajaran kewirausahaan koperasi sekolah dimulai dengan pemberian wawasan (pelatihan dan pendampingan). Kata Kunci: koperasi, kewirausahaan, siswa SMP